Dış ticarette liberalleşmenin ülke ekonomisine etkileri: Azerbaycan üzerine bir inceleme - Davudov, Murad (My University, 2001)
Bu tez çalışmasında ülke ekonomisinde özellikle de dış ticarette liberalleşmenin önemi incelenerek; bağımsızlığını yeni kazanan Azerbaycan Cumhuriyeti'nin uluslararası rekabet gücü hesaplandı. İlk önce liberalleşmenin tanımı, farklı iktisat ekollerinin liberalleşmeye bakışları ele alındı; Merkantilizm, Klasik ve Neo- Klasik dış ticaret teorileri incelendi İkinci bölümde dış ticarete yönelik politikalar; ithal ikamesi, ihracata dönük sanayileşme ve yeni korumacılık araştırıldı. Bir sonraki bölümde liberasyonun ülke ekonomisine pozitif ve negatif etkileri tartışıldı. Bu bağlamda tüketim, üretim, gelir dağılımı, ölçek ekonomileri, rekabet, büyüme, mali gelir, istihdam, ödemeler dengesi etkilerini açıklamaya çalıştık. Tezimin son bölümünde; Azerbaycan ekonomisinin bağımsızlık sonrası seyri, Azerbaycan ekonomisinde liberalleşme eğilimleri ve bu çerçevede yapılan gelişmeler ele alındı. Fiyat serbestleşmesi, özelleştirme ve yabancı sermaye yatırımlara değinildi. Piyasa ekonomisinin temel özellikleri, ülkenin liberasyon düzeyi incelendi. 1995-96 ve 1998-99 yıllarında Azerbaycan' ın ülkeler düzeyinde uluslararası rekabet edebilirliği hesaplandı. Son olarak Azerbaycan - Türkiye ekonomik ilişkiler tartışıldı, karşılıklı ticaretle ilgili bilgi vererek araştırmamızı tamamladık. 1997 yılında Azerbaycan' da çıkartılan Liberalleşme Yasasını da ek olarak ilave ettik.

The Effects Of Liberasation In Foreign Trade To The Economy of a Country: An Investigation Over Azerbaijan. In this study of thesis, we research the importance of liberalisation in the econumy of a country, especially in its foreign trade. Then, we computed the international competitive advantage of the Republic of Azerbaijan which has been acquired its independence recently. In the first chapter, we gave the definition of liberalisation and handled with views of different economic schools to liberalisation. We researched foreign trade theories of Merkantilist, Classical and Neoclassical schools. In the second chapter, we researched policies toward foreign trade, import substitution, industrialization toward export and new protectionism. In the later chapter, we discussed positive and negative effects of liberalisation to the economy of a country. With this manner, we tried to explain consumption, production, income distribution, economies of scale, competition, growth, fiscal revenue, employment and balance of payment effects. In the last chapter of my thesis, we tried to explain the condition of the economy of Azerbaijan after independenc, tendencies of liberaliation in Azerbaijan economy and studies to realise this. After we touched on liberalisation of prices, privatization and foreign capital investments. We researched basic features of market economics and the level of the liberalisation of the country. We computed the international competitiveness of Azerbaijan at the level of countries in the years of 1995-1996 and 1998-1999. At last, we discussed economic relations between Azerbaijan and Turkey. We completed our study of thesis by giving information mutual trade. We added the Act of Liberalisation which admitted in 1997 in Azerbaijan.
Keywords: AZERBAYCAN; Dış ticaret; DIŞ TİCARET-AZERBAYCAN; Ekonomi-Dış Ticaret; LİBERALİZM; Ticaret